FEATURES OF DIAGNOSTICS OF AGGRESSIVE BEHAVIOR IN CHILDREN 6-7 YEARS OLD - Rasulova Feruza Fayzullaevna (Innovate Conferences, 2025)
Brief analysis of the main approaches to the diagnosis of aggressive behavior is presented, the tasks of psychodiagnostic work with aggressive children, the main directions and methods are highlighted.
Keywords: aggressive behaviour, aggression, aggressive actions, correction of aggressive behaviour, correction methods.